The luminescence dating chronology of a deep core from Bosten Lake (NW China) in arid central Asia reveals lake evolution over the last 220 ka. (4th October 2016) - Li, Guoqiang; Duan, Yanwu; Huang, Xiaozhong; Buylaert, Jan‐Pieter; Peng, Wei; Madsen, David B.; Rao, Zhiguo; She, Linlin; Xie, Haichao; Chen, Jianhui; Chen, Fahu
Abstract : The lacustrine deposits of lakes in arid central Asia (ACA) potentially record palaeoclimatic changes on orbital and suborbital time scales, but such changes are still poorly understood due to the lack of reliable chronologies. Bosten Lake, the largest freshwater inland lake in China, is located in the southern Tianshan Mountains in central ACA. A 51.6‐m‐deep lacustrine succession was retrieved from the lake and 30 samples from the succession were used for luminescence dating to establish a chronology based on multi‐grain quartz OSL and K‐feldspar post‐IR IRSL (pIRIR290 ) dating. Quartz OSL ages were only used for samples from the upper part of the core. The K‐feldspar luminescence characteristics (dose recovery test, anomalous fading test, first IR stimulation temperature plateau test) are satisfactory and from the relationship amongst the quartz OSL, IR50 and pIRIR290 doses we infer that the feldspar signals are likely to be well bleached at deposition. Bacon age‐depth modelling was used to derive a chronology spanning the last c. 220 ka. The chronology, lithology and grain‐size proxy record indicate that Bosten Lake formed at least c. 220 ka ago and that lake levels fluctuated frequently thereafter. A stable deep lake occurred at c. 220, 210–180, c. 165, 70–60, 40–30 and 20–5 ka, while shallow levels occurred at c. 215, 180–165, 100–70, 60–40 and 30–20 ka. Bosten Lake levels decreased by at least 29 m and possibly the lake even dried up between c. 160 and c. 100 ka. We suggest that the water‐level fluctuations in the lakes of ACA may not respond directly to climatic changes and may be affected by a number of complex factors.